(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article discussed about Communicative Language teaching with a particular reference to the teaching and learning of German. The article deals with the educational management teaching process in Higher education. Research will explain to teachers the method of teaching German as a foreign language (GLF) in the classroom setting in such a way that students can communicate and practice knowledge in a spontaneous way, taking into account their real experiences. Communicative language teaching (CLT) is a language teaching method that emphasizes interaction as both the means and the goal of study. The article is illustrated clearly some examples of communicative activities which are given from the novels that can be used in a German class for non native learners of German. We can acknowledge about thoughts of great German linguistics and essential tips for learners.